FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMAMPUAN PERAWAT DALAM MELENGKAPI PENGKAJIAN AWAL KEPERAWATAN MEDICAL SURGICAL - Arni Nur Hidayah; Wasisto Utomo; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Assessment is the first step of the nursing process. The completeness of filling the assessment by nurses can improve health service and affect the quality of a hospital. This study aims to determine the factors associated with the nurses ability in completing medical surgical nursing initial assessment. The design of this research is descriptive correlation with cross sectional approach and total sampling used as the sampling technique. Measuring instrument used was questionnaires with the chi-square data analysis. The results of this study indicate that there was no relationship between education and nurses ability to complete nursing initial assessment the length of employment with value of 0.245 p > α (0.05), and there was also correlation to the length of employment and the nurses ability to complete nursing initial assessment with 0.047 p < α (0.05). Meanwhile, there was no relationship in terms of the reward to the nurses ability in completing nursing initial assessment with a value of 0.610 p > α (0.05). Conversely there was a relationship regarding to punishment with the nursing ability to complete nursing initial assessment by 0.01 p > α (0.05), and there was no association between the workload of the nurses ability and nursing initial assessment with a value of 0.248 p > α (0.05). The results of this study are expected to be the supporting data for parties involved and become a reference in developing nursing and further research on factors associated with nurses ability in completing nursing initial assessment.Keywords: Factors, Nursing initial assessment, Medical, Surgical.